The cultural imperative : global trends in the 21st century. - Lewis, Richard Donald, 1930- (S.l. : Intercultural press, 2007)
Those who extrapolate trends and predict the future say that economic, political and even genetic factors will determine the future of the world. But, in fact, culture makes the world go around, according to Richard D. Lewis, a well-traveled scholar who reflects here on the origins and implications of human cultures. Culture has deep roots in history, religion and language, so it will probably be a more potent factor in shaping the future than many observers grant. Now it is fashionable to say that cultures are coalescing into one global culture. This author strenuously opposes that easy assumption. He also offers a deeper look at Islamic culture in a post-Sept. 11 addendum.
Inhoudsopgave : From 2 000 000 B.C. to A.D.2000: The roots and routes of culture Culture and climate Culture and religion Cross-century worldviews Cultural spectacles Cultural black holes Cognitive processes The Pacific rim: The fourth cultural ecology The China phenomenon Americanization versus Asianization Culture and globalization Empires-Past, present and future After September 11
Keywords: Cultuur en maatschappij; Cultuur; Cultuurmanagement; Cultuurverschillen; Globalisering; Go International; International office